Indirect Calorimetry: History, Technology, and Application - Mtaweh, Haifa; Tuira, Lori; Floh, Alejandro A.; Parshuram, Christopher S. (Frontiers in Pediatrics, 2018)
Measurement of energy expenditure is important in order to determine basal metabolic rate and inform energy prescription provided. Indirect calorimetry is the reference standard and clinically recommended means to measure energy expenditure. This article reviews the historical development, technical, and logistic challenges of indirect calorimetry measurement, and provides case examples for practicing clinicians. Formulae to estimate energy expenditure are highly inaccurate and reinforce the role of the indirect calorimetry and the importance of understanding the strength and limitation of the method and its application.